Korelasi Luaran dengan Ketebalan dan Lokasi Perdarahan Subaraknoid pada Pasien Cedera Kepala di RSUD Arifin Achmad - Andrea Valentino (Jurnal Ilmu Kedokteran, 2016)
Subarachnoid hemorrhage (SAH)in head injury is a very common case. Research showed that 33% moderate andsevere head injury patients had SAH during initial CT scan. A prospective study was performed on 37 head injurypatients with SAH which had been treated in Arifin Achmad Hospital during January to June 2014 period. Bivariableanalysis that was used in this research was an unpaired categorical analytic statistical test, the chi square test. Meanwhile,multivariable analysis used was multiple logistic regression test. Significance was determined based on p value,which was d”0.05, and confidence interval (CI) of 95%. There were unfavourable outcome upon head injury patientswith SAH of >5mm thickness (p=0,028) and located at cerebral hemisphere and basal cistern (p=0,001). Thicknessand SAH location was found to be associated with head injury patient outcome. SAH thickness of > 5mm againstoutcome had a stronger association than location as a factor.